Esteban Cantu and the Mexican Revolution in Baja California Norte, 1910-1920 - Werne, Joseph Richard, 1943- (Book collections on Project MUSE., 2020)
Outfoxing all other military and political personnel in the territory of Baja California Norte, Colonel Esteban Cantú, on becoming governor, astutely played the leaders of the Mexican Revolution one against another. A compelling figure in the Mexican Revolution, he maintained his independence from Mexico City until he was forced from office in August 1920. While Cantú was appointed governor by Venustiano Carranza, Pancho Villa, and Eulalio Gutierrez of the Convention Government, he followed their orders only when it suited him and published the laws of the government in Mexico City to give the appearance that he was loyal to the central power when in fact he was not. He was more concerned with neighboring Sonora and supported every anti-central government movement in that state to secure his own independence. When he gained power, Cantú faced an indescribable morass of crime and immorality in Tijuana and Mexicali: white slavery and prostitution; opium dens; cocaine, morphine, and heroin dealers; and gambling halls, saloons, and dives of all descriptions. Governor Cantú either licensed many of these or became connected to them in some other way, personally profiting from such activities but also employing much of this revenue to create the territory's first reliable infrastructure. This engaging account reveals the complexity of the Mexican Revolution, with a cast of characters that includes officers and officials of the Porfirian regime, revolutionaries and counterrevolutionaries, US investors, crackpots, German spies, Japanese schemers, Chinese workers, and purveyors of every sort of vice. --